Penyebab Kasus Cerai Gugat: Studi di Pengadilan Agama Kota Metro - Arsyad, Mufid; Ja'far, A. Kumedi (AL-SULTHANIYAH, 2025)
This research is based on the increasing divorce rates, where external factors such as economic instability, social pressure, and psychological incompatibility further exacerbate marital conflicts. The aim of this research is to identify and analyze the influence of these three factors in the decision-making process of couples divorcing. The research employs a qualitative method with a descriptive-analytical approach, supported by both primary and secondary data collected through interviews and documentation. The results show that economic difficulties, social neglect, and psychological incompatibility play a significant role in triggering divorce. Economic factors such as the inability of couples to meet basic needs, social factors such as stigma and family pressure, and psychological factors such as lack of effective communication, are the primary triggers for the decision to separate. In conclusion, divorce is not only caused by individual differences but also by collective pressures that disrupt marital balance. The implications of this research suggest the need for policies that support couples in facing socio-economic challenges to reduce divorce rates and maintain family harmony.